2000
DOI: 10.1046/j.1432-1327.2000.01219.x
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of non‐Aβ component of Alzheimer's disease amyloid, and N‐terminal fragments thereof, correlates to formation of β‐sheet structure and fibrils

Abstract: The non-Ab component of Alzheimer's disease amyloid (NAC) and its precursor a-synuclein have been linked to amyloidogenesis in Alzheimer's disease (AD), Parkinson's disease (PD) and dementia with Lewy bodies (DLB). Previously we have shown that NAC forms b-sheet structures and fibrils [El-Agnaf, O.M.A., Bodles, A.M., Guthrie, D.J.S., Harriott, P. & Irvine, G.B. (1998) Eur. J. Biochem. 258, 157±163]. As a measure of their neurotoxic potential we have examined the ability of fresh and aged NAC and fragments ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 28 publications
4
65
0
Order By: Relevance
“…The fibrillar state of RCMκ-CN is cytotoxic to PC12 cells Previous research has shown that amyloid fibril-forming proteins are more toxic in an aggregated, fibrillar state compared to their native, non-fibrillar form (El-Agnaf et al 1998;Bodles et al 2000;Bucciantini et al 2002;Novitskaya et al 2006;Chimon et al 2007). To determine whether this was also the case for RCMκ-CN, PC12 cells were treated with RCMκ-CN in its native state and following incubation in phosphate buffer (50 mM, pH 7.4) at 37°C for 20 h (Thorn et al 2005;Ecroyd et al 2007Ecroyd et al , 2008, conditions under which it forms fibrils (i.e., fibrillar RCMκ-CN).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fibrillar state of RCMκ-CN is cytotoxic to PC12 cells Previous research has shown that amyloid fibril-forming proteins are more toxic in an aggregated, fibrillar state compared to their native, non-fibrillar form (El-Agnaf et al 1998;Bodles et al 2000;Bucciantini et al 2002;Novitskaya et al 2006;Chimon et al 2007). To determine whether this was also the case for RCMκ-CN, PC12 cells were treated with RCMκ-CN in its native state and following incubation in phosphate buffer (50 mM, pH 7.4) at 37°C for 20 h (Thorn et al 2005;Ecroyd et al 2007Ecroyd et al , 2008, conditions under which it forms fibrils (i.e., fibrillar RCMκ-CN).…”
Section: Resultsmentioning
confidence: 99%
“…In cell models of AD, PD, and prion diseases, the amyloidogenic proteins associated with these diseases are toxic in their oligomeric and/or fibrillar form but not in their monomeric state (El-Agnaf et al 1998;Bodles et al 2000;Novitskaya et al 2006;Chimon et al 2007). Furthermore, fibrillar aggregates of non-disease-related proteins are toxic, which suggests that toxicity is related to the mechanism of fibril formation and/or the overall fibril structure (Bucciantini et al 2002) rather than the native state of the proteins that form them.…”
Section: Introductionmentioning
confidence: 99%
“…However, peak III is absent from b-syn, which coincides with the difference at residues 71 and 72 and, most notably, the absence of the b-strand-favorable amino acids found in a-syn at residues 73-83. Peak III, which is the largest of the three peaks, locates to the region reported to dominate the fibrillogenic capacity of a-syn (Han et al 1995;Iwai et al 1995;El-Agnaf et al 1998a,b;Bodles et al 2000Bodles et al , 2001Giasson et al 2001;Du et al 2003). b-Syn is reproducibly nonfibrillogenic (Goedert 2001) and is absent from Lewy bodies (Spillantini et al 1997).…”
Section: A-synuclein Vs B-synucleinmentioning
confidence: 95%
“…The most common hypothesis for the mechanism of a-Syn oligomer toxicity is that oligomers can create pores in membranes, which increases cell permeability to ions from the extracellular space leading to cell death (21,27). This hypothesis is largely based on some species of a-Syn oligomers that are annular or pore-like with outer diameters of 10-12 nm and inner diameters of 2 nm, respectively (29,31). These features may lead to the increased but nonspecific ion permeability observed with a-Syn overexpressing cells (32).…”
Section: Aggregation and Oligomersmentioning
confidence: 99%